Optimization of enzymatic hydrolysis conditions for increasing the efficiency of dry matter extracted from limonia acidissima pulp by combined cellulase -pectinase enzymes using response surface methodology - Nguyen, Pham Bao; Dao, Dong Thi Anh (Vietnam Journal of Science and Technology, 2017)
The Limonia acidissima (L. acidissima) fruit is rich nutrient and bioactive compounds. Our research on the hydrolysis of L. acidissima pulp by combined cellulase and pectinase enzymes to increase the yield of dry matter and bioactive compounds for health benefit is important. In this study, the hydrolysis conditions by combined enzymes for the dry matter recovery were optimized by response surface methodology (RSM). The independent variables were coded pH (X1), incubation temperature (X2), the total content of combined cellulase-pectinase (X3) (with the ratio of cellulase/pectinase was 1/1), and hydrolysis time (X4). The results of the analysis of variance (ANOVA) showed that the variables actively affected the efficiency of extracted dry matter. The optimal conditions of hydrolysis were derived at x1 = 4.2, x2 = 45 oC, x3 = 1.6 % (v/dwt), x4 = 120minutes, respectively in the efficiency of the prediction model was 54.76 %. that increased 20.89 % in compared with non-enzymatic extraction. Besides, the recovery efficiency of carbohydrates was 87.74 %. Further, all the content of extracted phenolic content (TPC), carotenoic and DPPH and ABTS radical scavenging activity highly increased. That reached 106.7mg GAE, 86.6mg, 67.1 and 102.1 mg trolox equivalent antioxidant capacity (TEAC) from 100g L. acidissima pulp respectively.